A hot melt adhesive film for sealing the catalyst layer of a hydrogen fuel cell

By forming a polystyrene molecular chain under the action of ammonium persulfate and sodium bisulfite and adding reinforced fillers, the shrinkage problem caused by long-term soaking of hot melt adhesive in hydrogen fuel cell is solved, and the problem of shrinkage caused by long-term soaking of hot melt adhesive in hydrogen fuel cell is achieved. It has better edge sealing effect and energy conversion efficiency.

CN115975518BActive Publication Date: 2025-02-11JIANGSU HUIFENG ENVIRONMENTAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211593829.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-13
Publication Date
2025-02-11
Estimated Expiration
2042-12-13

AI Technical Summary

Technical Problem

At this stage, the hot melt adhesive is soaked in ionic water for a long time in hydrogen fuel cells, causing the hot melt adhesive to shrink, which in turn affects the edge sealing effect, resulting in fuel leakage or protons randomly diffusing, reducing energy conversion efficiency.

Method used

Modified resin and styrene react under the action of ammonium persulfate and sodium bisulfite to form a polystyrene molecular chain, and reinforcing filler is added. The self-initiated hot melt adhesive is terminated by reacting isocyanate groups with the modified resin terminal hydroxyl group. Initiate cracking, reduce the acid value and ester concentration of the material, and prevent the shrinkage of the hot melt adhesive and the diffusion of ionic water.

Benefits of technology

It effectively prevents the shrinkage of the hot melt adhesive, ensures the edge sealing effect of the hydrogen fuel cell, prevents the leakage of ionic water and the random diffusion of protons, and improves the energy conversion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE002
    Figure DEST_PATH_IMAGE002
Patent Text Reader

Abstract

The invention discloses a hot melt adhesive film for sealing a catalyst layer of a hydrogen fuel cell. The double bonds of the modified resin side chain and styrene are polymerized under the action of ammonium persulfate and sodium bisulfite to form a polystyrene molecular chain in the side chain. A reinforcing filler is added, and the isocyanate group on the surface of the reinforcing filler reacts with the terminal hydroxyl group of the modified resin, and then the film is formed by banburying. The polycarbodiimide on the surface of the reinforcing filler can react with the carboxyl group generated by the hydrolysis of the ester group in the hot melt adhesive film, thereby terminating the self-initiated cracking of the hot melt adhesive, reducing the acid value of the material, and reducing the concentration of the ester group in the molecular chain, thereby reducing the possibility of ester group hydrolysis, so that when the hydrogen fuel cell is working, the hot melt adhesive is in contact with ionized water for a long time, and the hot melt adhesive will not shrink. The porous cavity structure of the reinforcing filler effectively prevents the ionized water from diffusing from the sealing part of the catalyst layer, thereby ensuring the working efficiency of the hydrogen fuel cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen fuel cell preparation, and in particular to a hot melt adhesive film for sealing a hydrogen fuel cell catalyst layer. Background Art

[0002] A hydrogen fuel cell is a battery that can convert chemical energy into electrical energy, similar to an ordinary battery, but it is quite different from an ordinary battery. It uses a catalyst to promote the redox reaction of the fuel, continuously generates current, and then plays the role of generating electricity. In this conversion process, there is no conversion of thermal kinetic energy, so the hydrogen fuel cell is not affected by the Carnot cycle, so the hydrogen fuel cell can achieve a very high energy conversion. Theoretically, as long as the hydrogen fuel cell can obtain a continuous supply of fuel and oxidant, it can output electrical energy continuously and stably. Some hydrogen fuel cells need to use hot melt adhesive to seal the catalyst layer during the preparation process to ensure that the fuel can accurately pass through the catalyst layer and the proton exchange membrane. Since the hydrogen fuel cell contains ionized water, the hot melt adhesive will be immersed in ionized water for a long time, and the traditional PET hot melt adhesive will be hydrolyzed, causing the hot melt adhesive to shrink, which will affect the sealing effect, so that the fuel passes through the catalyst layer and penetrates from the side of the catalyst layer, and then cannot accurately pass through the proton exchange membrane, thereby reducing the energy conversion efficiency. Summary of the invention

[0003] The purpose of the present invention is to provide a hot melt adhesive film for sealing the catalyst layer of a hydrogen fuel cell, which solves the problem that the hot melt adhesive shrinks when immersed in ion water for a long time, resulting in leakage of ion water or random diffusion of protons.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A hydrogen fuel cell catalyst layer sealing hot melt adhesive film is made by the following steps:

[0006] The modified resin is dissolved in N-methylpyrrolidone, styrene, ammonium persulfate and sodium bisulfite are added, and nitrogen is introduced for protection. The reaction is carried out for 5-6 hours at a speed of 200-300r / min and a temperature of 70-75°C. After reinforcing fillers are added and mixed evenly, N-methylpyrrolidone is removed by distillation, and then the mixture is kneaded at a temperature of 230°C for 2-3 hours and pressed into film.

[0007] Furthermore, the mass ratio of the modified resin, styrene, ammonium persulfate and sodium bisulfite is 5:20:0.52:0.43, and the amount of the reinforcing filler is 5-8% of the mass of the modified resin.

[0008] Further, the modified resin is prepared by the following steps:

[0009] Step A1: 4,4'-dimethylbiphenyl and concentrated sulfur solution are mixed, stirred and nitric acid solution is added dropwise at a speed of 60-120 r / min and a temperature of 20-25°C, and the mixture is reacted for 3-5 hours, cooled in an ice water bath, and the filtrate is removed by filtration to obtain intermediate 1; intermediate 1, sodium dichromate and deionized water are mixed uniformly, stirred and refluxed at a speed of 150-200 r / min and a temperature of 105-110°C, concentrated sulfuric acid is added dropwise, and the mixture is refluxed for 1-2 hours to obtain intermediate 2;

[0010] Step A2: The intermediate 2, sodium sulfide nonahydrate, sodium bicarbonate and deionized water are mixed uniformly, reacted at a temperature of 80-85° C. for 40-50 minutes, heated to boiling, filtered to remove the filter residue, and the pH value of the filtrate is adjusted to 7, and then the pH value is adjusted to 4.5-5 to obtain the intermediate 3, the intermediate 3, isophthalic acid, ethylene glycol, diethylene glycol and tetrabutyl titanate are mixed uniformly, reacted at a speed of 150-200 r / min and a temperature of 95-105° C. for 30-40 minutes, and then heated to 200-220° C. and continued to react for 3-4 hours to obtain an alcohol ester;

[0011] Step A3: Evenly mix the alcohol ester, acetone, acrylic acid and 1-hydroxybenzotriazole, react for 2-3 hours at a rotation speed of 200-300 r / min and a temperature of 40-50° C., distill off the acetone, and then react for 8-10 hours at a temperature of 240-265° C. and a pressure of 500-600 Pa, add acetone, filter and remove the filtrate, and obtain a modified resin.

[0012] Furthermore, the dosage ratio of 4,4'-dimethylbiphenyl, concentrated sulfur solution and nitric acid solution described in step A1 is 0.02mol:50mL:20mL, the mass fraction of concentrated sulfur solution is 95%, the mass fraction of nitric acid solution is 55%, intermediate 1, sodium dichromate, deionized water and concentrated sulfuric acid 21g:98g:100mL:200mL, and the mass fraction of concentrated sulfuric acid is 98%.

[0013] Furthermore, the molar ratio of intermediate 2, sodium sulfide nonahydrate and sodium bicarbonate described in step A2 is 1:2:1.3, the molar ratio of intermediate 3, isophthalic acid, ethylene glycol and diethylene glycol is 1:1:1.6:2, and the amount of tetrabutyl titanate is 0.055-0.075% of the total mass of intermediate 3, isophthalic acid, ethylene glycol and diethylene glycol.

[0014] Furthermore, the molar ratio of the amino group, acrylic acid and 1-hydroxybenzotriazole on the alcohol ester in step A3 is 1:1:1.1.

[0015] Further, the reinforcing filler is prepared by the following steps:

[0016] Step B1: The porous ceramic powder is dispersed in deionized water, stirred at a speed of 200-300 r / min and a temperature of 40-50° C., KH560 is added, stirred for 1-1.5 hours, and the filtrate is removed by filtering. The substrate is dispersed in xylene, KH550 is added, and the reaction is carried out for 4-6 hours at a speed of 150-200 r / min and a pH value of 10-11 to obtain a pretreated filler;

[0017] Step B2: Disperse the pretreated filler in dimethyl sulfoxide, add KH550 at a speed of 200-300 r / min and a temperature of 60-65° C., stir for 10-15 hours, cool to 20-25° C., add ammonium fluoride, and continue to react for 20-25 hours to obtain a modified filler;

[0018] Step B3: Tetramethylbenzene diisocyanate is added to a reaction kettle, and nitrogen is introduced for protection. At a rotation speed of 150-200 r / min and a temperature of 180-190° C., 3-methyl-1-phenyl-2-phosphocyclopentene-1-oxide is added with stirring, and the reaction is carried out for 10-15 hours to obtain intermediate 4. Intermediate 4 is dissolved in acetone, and a modified filler is added. After ultrasonic treatment at a frequency of 30-40 kHz for 3-5 hours, the filtrate is filtered to remove the filtrate to obtain a reinforced filler.

[0019] The reaction process is as follows:

[0020]

[0021] Furthermore, the amount of KH560 used in step B1 is 5-8% of the porous ceramic powder, and the molar ratio of KH560 to KH550 is 1:1.

[0022] Furthermore, the usage ratio of the pretreated filler, KH550 and ammonium fluoride in step B2 is 1 g:5 mL:0.15 g.

[0023] Furthermore, the amount of 3-methyl-1-phenyl-2-phospholene-1-oxide used in step B3 is 1-3% of the mass of tetramethylxylylene diisocyanate, and the mass ratio of intermediate 4 to modified filler is 5:1.

[0024] Beneficial effects of the present invention: A hydrogen fuel cell catalyst layer sealing hot melt adhesive film prepared by the present invention is prepared by polymerizing the double bonds of the modified resin side chain and styrene under the action of ammonium persulfate and sodium bisulfite to form a polystyrene molecular chain on the side chain, and then adding a reinforcing filler, and the isocyanate group on the surface of the reinforcing filler reacts with the terminal hydroxyl group of the modified resin, and then kneading and pressing the film to form, the modified resin is nitrated with 4,4'-dimethylbiphenyl as a raw material, and a nitro group is grafted on the benzene ring to obtain an intermediate 1, and then under the action of sodium chromate and concentrated sulfuric acid, the methyl group is converted into a carboxyl group to obtain an intermediate 2, and the intermediate 2 is reduced to convert the nitro group into an amino group to obtain an intermediate 3, and the intermediate 3, isophthalic acid, ethylene glycol and diethylene glycol are esterified to form an alcohol ester, and the alcohol ester is reacted with acrylic acid, so that the amino group on the alcohol ester and the carboxyl group on the acrylic acid are dehydrated and condensed, and then high-temperature polycondensation is performed to obtain a modified resin, and the reinforcing filler is treated with KH560 with porous ceramic as a raw material. A large number of epoxy groups are grafted on the surface of porous ceramics, and KH550 is added under alkaline conditions, and the amino groups on KH550 react with the epoxy groups to obtain a pretreated filler, and then KH550 is added for hydrolysis and copolymerization to form a cage-type Si-O-Si structure, and tetramethylbenzene dimethyl isocyanate is condensed to obtain intermediate 4. When intermediate 4 is mixed with a modified filler, the amino groups on the modified filler react with the isocyanate on the intermediate 4 to form a reinforced filler with isocyanate groups grafted on the surface, and the polycarbodiimide on the surface of the reinforced filler can react with the carboxyl groups produced by the hydrolysis of the ester groups in the hot melt adhesive film, thereby terminating the self-initiated cracking of the hot melt adhesive, reducing the acid value of the material, and reducing the concentration of the ester groups in the molecular chain, thereby reducing the possibility of ester hydrolysis, so that when the hydrogen fuel cell is working, the hot melt adhesive is in contact with ionized water for a long time, and the hot melt adhesive will not shrink, and the porous cavity structure of the reinforced filler effectively prevents the diffusion of ionized water from the sealing part of the catalyst layer, thereby ensuring the working efficiency of the hydrogen fuel cell. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] A hydrogen fuel cell catalyst layer sealing hot melt adhesive film is made by the following steps:

[0028] The modified resin was dissolved in N-methylpyrrolidone, styrene, ammonium persulfate and sodium bisulfite were added, and nitrogen was introduced for protection. The reaction was carried out at a speed of 200 r / min and a temperature of 70°C for 5 hours. After reinforcing fillers were added and mixed evenly, N-methylpyrrolidone was removed by distillation. The mixture was then kneaded at a temperature of 230°C for 2 hours and pressed into film.

[0029] The mass ratio of the modified resin, styrene, ammonium persulfate and sodium bisulfite is 5:20:0.52:0.43, and the amount of the reinforcing filler is 5% of the mass of the modified resin.

[0030] The modified resin is prepared by the following steps:

[0031] Step A1: 4,4'-dimethylbiphenyl and concentrated sulfur solution are mixed, stirred at a speed of 60 r / min and a temperature of 20°C, and a nitric acid solution is added dropwise, and the mixture is reacted for 3 hours, and then cooled in an ice water bath, and the filtrate is filtered to remove the filtrate to obtain intermediate 1. Intermediate 1, sodium dichromate and deionized water are mixed uniformly, stirred at a speed of 150 r / min and a temperature of 105°C, and concentrated sulfuric acid is added dropwise, and the mixture is refluxed for reaction for 1 hour to obtain intermediate 2;

[0032] Step A2: The intermediate 2, sodium sulfide nonahydrate, sodium bicarbonate and deionized water are mixed uniformly, reacted at a temperature of 80°C for 40 minutes, heated to boiling, filtered to remove the filter residue, and the pH value of the filtrate is adjusted to 7, and then the pH value is adjusted to 4.5 to obtain the intermediate 3, the intermediate 3, isophthalic acid, ethylene glycol, diethylene glycol and tetrabutyl titanate are mixed uniformly, reacted at a speed of 150 r / min and a temperature of 95°C for 30 minutes, and then heated to 200°C and continued to react for 3 hours to obtain an alcohol ester;

[0033] Step A3: Evenly mix the alcohol ester, acetone, acrylic acid and 1-hydroxybenzotriazole, react at a speed of 200 r / min and a temperature of 40° C. for 2 h, distill off the acetone, and then react at a temperature of 240° C. and a pressure of 500 Pa for 8 h, add acetone and filter to remove the filtrate to obtain a modified resin.

[0034] The dosage ratio of 4,4'-dimethylbiphenyl, concentrated sulfur solution and nitric acid solution described in step A1 is 0.02mol:50mL:20mL, the mass fraction of concentrated sulfur solution is 95%, the mass fraction of nitric acid solution is 55%, intermediate 1, sodium dichromate, deionized water and concentrated sulfuric acid 21g:98g:100mL:200mL, and the mass fraction of concentrated sulfuric acid is 98%.

[0035] The molar ratio of intermediate 2, sodium sulfide nonahydrate and sodium bicarbonate described in step A2 is 1:2:1.3, the molar ratio of intermediate 3, isophthalic acid, ethylene glycol and diethylene glycol is 1:1:1.6:2, and the amount of tetrabutyl titanate used is 0.055% of the sum of the mass of intermediate 3, isophthalic acid, ethylene glycol and diethylene glycol.

[0036] The molar ratio of the amino group on the alcohol ester, acrylic acid and 1-hydroxybenzotriazole in step A3 is 1:1:1.1.

[0037] The reinforcing filler is prepared by the following steps:

[0038] Step B1: The porous ceramic powder is dispersed in deionized water, stirred at a speed of 200 r / min and a temperature of 40°C, and KH560 is added. After stirring for 1 hour, the filtrate is filtered to remove the filtrate, the substrate is dispersed in xylene, KH550 is added, and the reaction is carried out at a speed of 150 r / min and a pH value of 10 for 4 hours to obtain a pretreated filler;

[0039] Step B2: Disperse the pretreated filler in dimethyl sulfoxide, add KH550 at a speed of 200 r / min and a temperature of 60°C, stir for 10 hours, cool to 20°C, add ammonium fluoride, and continue to react for 20 hours to obtain a modified filler;

[0040] Step B3: Tetramethylbenzene diisocyanate was added into a reaction kettle, nitrogen was introduced for protection, 3-methyl-1-phenyl-2-phosphole-1-oxide was added under stirring at a rotation speed of 150 r / min and a temperature of 180°C, and the reaction was carried out for 10 hours to obtain intermediate 4. Intermediate 4 was dissolved in acetone, and a modified filler was added. After ultrasonic treatment at a frequency of 30 kHz for 3 hours, the filtrate was filtered to remove the filtrate to obtain a reinforced filler.

[0041] The amount of KH560 used in step B1 is 5% of the porous ceramic powder, the molar ratio of KH560 to KH550 is 1:1, and the porous ceramic powder is produced by Wuxi Daxin Environmental Protection Materials Co., Ltd.

[0042] The usage ratio of the pretreated filler, KH550 and ammonium fluoride in step B2 is 1 g:5 mL:0.15 g.

[0043] The amount of 3-methyl-1-phenyl-2-phospholene-1-oxide used in step B3 is 1% of the mass of tetramethylxylylene diisocyanate, and the mass ratio of intermediate 4 to modified filler is 5:1.

[0044] Example 2

[0045] A hot melt adhesive film for sealing a hydrogen fuel cell catalyst layer is made by the following steps:

[0046] The modified resin was dissolved in N-methylpyrrolidone, styrene, ammonium persulfate and sodium bisulfite were added, and nitrogen was introduced for protection. The reaction was carried out at a speed of 200 r / min and a temperature of 75°C for 5 hours. After reinforcing fillers were added and mixed evenly, N-methylpyrrolidone was removed by distillation. The mixture was then kneaded at a temperature of 230°C for 2 hours and pressed into film.

[0047] The mass ratio of the modified resin, styrene, ammonium persulfate and sodium bisulfite is 5:20:0.52:0.43, and the amount of the reinforcing filler is 6% of the mass of the modified resin.

[0048] The modified resin is prepared by the following steps:

[0049] Step A1: 4,4'-dimethylbiphenyl and concentrated sulfur solution are mixed, stirred and nitric acid solution is added dropwise at a speed of 60 r / min and a temperature of 25°C, and the mixture is reacted for 4 hours, then cooled in an ice water bath, and the filtrate is removed by filtration to obtain intermediate 1. Intermediate 1, sodium dichromate and deionized water are mixed uniformly, stirred and refluxed at a speed of 150 r / min and a temperature of 108°C, and concentrated sulfuric acid is added dropwise, and the mixture is refluxed for 2 hours to obtain intermediate 2;

[0050] Step A2: The intermediate 2, sodium sulfide nonahydrate, sodium bicarbonate and deionized water are mixed uniformly, reacted at a temperature of 80°C for 45 minutes, heated to boiling, filtered to remove the filter residue, and the pH value of the filtrate is adjusted to 7, and then the pH value is adjusted to 4.5 to obtain the intermediate 3, the intermediate 3, isophthalic acid, ethylene glycol, diethylene glycol and tetrabutyl titanate are mixed uniformly, reacted at a speed of 200 r / min and a temperature of 100°C for 35 minutes, and then heated to 210°C and continued to react for 3 hours to obtain an alcohol ester;

[0051] Step A3: Evenly mix the alcohol ester, acetone, acrylic acid and 1-hydroxybenzotriazole, react at a speed of 300 r / min and a temperature of 45° C. for 3 h, distill off the acetone, and then react at a temperature of 250° C. and a pressure of 550 Pa for 9 h, add acetone and filter to remove the filtrate to obtain a modified resin.

[0052] The dosage ratio of 4,4'-dimethylbiphenyl, concentrated sulfur solution and nitric acid solution described in step A1 is 0.02mol:50mL:20mL, the mass fraction of concentrated sulfur solution is 95%, the mass fraction of nitric acid solution is 55%, intermediate 1, sodium dichromate, deionized water and concentrated sulfuric acid 21g:98g:100mL:200mL, and the mass fraction of concentrated sulfuric acid is 98%.

[0053] The molar ratio of intermediate 2, sodium sulfide nonahydrate and sodium bicarbonate described in step A2 is 1:2:1.3, the molar ratio of intermediate 3, isophthalic acid, ethylene glycol and diethylene glycol is 1:1:1.6:2, and the amount of tetrabutyl titanate used is 0.065% of the sum of the mass of intermediate 3, isophthalic acid, ethylene glycol and diethylene glycol.

[0054] The molar ratio of the amino group on the alcohol ester, acrylic acid and 1-hydroxybenzotriazole in step A3 is 1:1:1.1.

[0055] The reinforcing filler is prepared by the following steps:

[0056] Step B1: The porous ceramic powder is dispersed in deionized water, stirred at a speed of 200 r / min and a temperature of 45°C, and KH560 is added. After stirring for 1.5 hours, the filtrate is filtered to remove the filtrate, the substrate is dispersed in xylene, KH550 is added, and the reaction is carried out at a speed of 150 r / min and a pH value of 11 for 5 hours to obtain a pretreated filler;

[0057] Step B2: Disperse the pretreated filler in dimethyl sulfoxide, add KH550 at a speed of 200 r / min and a temperature of 65°C, stir for 10 hours, cool to 25°C, add ammonium fluoride, and continue to react for 20 hours to obtain a modified filler;

[0058] Step B3: Tetramethylbenzene diisocyanate was added into a reaction kettle, and nitrogen was introduced for protection. At a rotation speed of 200 r / min and a temperature of 185°C, 3-methyl-1-phenyl-2-phosphole-1-oxide was added with stirring, and the reaction was carried out for 10 hours to obtain intermediate 4. Intermediate 4 was dissolved in acetone, and a modified filler was added. After ultrasonic treatment at a frequency of 35 kHz for 4 hours, the filtrate was filtered to remove the filtrate to obtain a reinforced filler.

[0059] The amount of KH560 used in step B1 is 6% of the porous ceramic powder, the molar ratio of KH560 to KH550 is 1:1, and the porous ceramic powder is produced by Wuxi Daxin Environmental Protection Materials Co., Ltd.

[0060] The amount ratio of the pretreated filler, KH550 and ammonium fluoride described in step B2 is 1g:5mL:0.15g.

[0061] The amount of 3-methyl-1-phenyl-2-phospholene-1-oxide used in step B3 is 2% of the mass of tetramethylxylylene diisocyanate, and the mass ratio of intermediate 4 to modified filler is 5:1.

[0062] Example 3

[0063] A hydrogen fuel cell catalyst layer sealing hot melt adhesive film is made by the following steps:

[0064] The modified resin was dissolved in N-methylpyrrolidone, styrene, ammonium persulfate and sodium bisulfite were added, and nitrogen was introduced for protection. The reaction was carried out at a speed of 300 r / min and a temperature of 75°C for 6 hours. After reinforcing fillers were added and mixed evenly, N-methylpyrrolidone was removed by distillation. The mixture was then kneaded at a temperature of 230°C for 3 hours and pressed into film.

[0065] The mass ratio of the modified resin, styrene, ammonium persulfate and sodium bisulfite is 5:20:0.52:0.43, and the amount of the reinforcing filler is 8% of the mass of the modified resin.

[0066] The modified resin is prepared by the following steps:

[0067] Step A1: 4,4'-dimethylbiphenyl and concentrated sulfur solution are mixed, stirred and nitric acid solution is added dropwise at a speed of 120 r / min and a temperature of 25°C, and the mixture is reacted for 5 hours, cooled in an ice water bath, and the filtrate is removed by filtration to obtain intermediate 1. Intermediate 1, sodium dichromate and deionized water are mixed uniformly, stirred and refluxed at a speed of 200 r / min and a temperature of 110°C, concentrated sulfuric acid is added dropwise, and the mixture is refluxed for 2 hours to obtain intermediate 2;

[0068] Step A2: The intermediate 2, sodium sulfide nonahydrate, sodium bicarbonate and deionized water are mixed uniformly, reacted at a temperature of 85° C. for 50 minutes, heated to boiling, filtered to remove the filter residue, and the pH value of the filtrate is adjusted to 7, and then the pH value is adjusted to 5 to obtain the intermediate 3, and the intermediate 3, isophthalic acid, ethylene glycol, diethylene glycol and tetrabutyl titanate are mixed uniformly, reacted at a speed of 200 r / min and a temperature of 105° C. for 40 minutes, and then heated to 220° C. and continued to react for 4 hours to obtain an alcohol ester;

[0069] Step A3: Evenly mix the alcohol ester, acetone, acrylic acid and 1-hydroxybenzotriazole, react at a speed of 300 r / min and a temperature of 50° C. for 3 h, distill off the acetone, and then react at a temperature of 265° C. and a pressure of 600 Pa for 10 h, add acetone, filter and remove the filtrate, and obtain a modified resin.

[0070] The dosage ratio of 4,4'-dimethylbiphenyl, concentrated sulfur solution and nitric acid solution described in step A1 is 0.02mol:50mL:20mL, the mass fraction of concentrated sulfur solution is 95%, the mass fraction of nitric acid solution is 55%, intermediate 1, sodium dichromate, deionized water and concentrated sulfuric acid 21g:98g:100mL:200mL, and the mass fraction of concentrated sulfuric acid is 98%.

[0071] The molar ratio of intermediate 2, sodium sulfide nonahydrate and sodium bicarbonate described in step A2 is 1:2:1.3, the molar ratio of intermediate 3, isophthalic acid, ethylene glycol and diethylene glycol is 1:1:1.6:2, and the amount of tetrabutyl titanate used is 0.075% of the total mass of intermediate 3, isophthalic acid, ethylene glycol and diethylene glycol.

[0072] The molar ratio of the amino group on the alcohol ester, acrylic acid and 1-hydroxybenzotriazole in step A3 is 1:1:1.1.

[0073] The reinforcing filler is prepared by the following steps:

[0074] Step B1: The porous ceramic powder is dispersed in deionized water, stirred at a speed of 300 r / min and a temperature of 50°C, and KH560 is added. After stirring for 1.5 hours, the filtrate is removed by filtration, the substrate is dispersed in xylene, KH550 is added, and the reaction is carried out at a speed of 200 r / min and a pH value of 11 for 6 hours to obtain a pretreated filler;

[0075] Step B2: Disperse the pretreated filler in dimethyl sulfoxide, add KH550 at a speed of 300 r / min and a temperature of 65°C, stir for 15 hours, cool to 25°C, add ammonium fluoride, and continue to react for 25 hours to obtain a modified filler;

[0076] Step B3: Tetramethylbenzene diisocyanate was added into a reaction kettle, nitrogen was introduced for protection, 3-methyl-1-phenyl-2-phosphole-1-oxide was added under stirring at a speed of 200 r / min and a temperature of 190°C, and the reaction was carried out for 15 hours to obtain intermediate 4. Intermediate 4 was dissolved in acetone, and a modified filler was added. After ultrasonic treatment at a frequency of 40 kHz for 5 hours, the filtrate was filtered to remove the filtrate to obtain a reinforced filler.

[0077] The amount of KH560 used in step B1 is 8% of the porous ceramic powder, the molar ratio of KH560 to KH550 is 1:1, and the porous ceramic powder is produced by Wuxi Daxin Environmental Protection Materials Co., Ltd.

[0078] The amount ratio of the pretreated filler, KH550 and ammonium fluoride described in step B2 is 1g:5mL:0.15g.

[0079] The amount of 3-methyl-1-phenyl-2-phospholene-1-oxide used in step B3 is 3% of the mass of tetramethylxylylene diisocyanate, and the mass ratio of intermediate 4 to modified filler is 5:1.

[0080] Comparative Example 1

[0081] Compared with Example 1, this comparative example uses graphene oxide instead of the reinforcing filler, and the remaining steps are the same.

[0082] Comparative Example 2

[0083] Compared with Example 1, this comparative example uses modified resin for direct film pressing.

[0084] The samples of Example 1-3 and Comparative Example 1-2 were made into samples with a thickness of 20 μm and an area of ​​2×2 cm. The samples were immersed in water at a temperature of 80° C. for 300 h, 500 h, 1000 h, and 2000 h, respectively, and the shrinkage of the samples was observed. The results are shown in the following table.

[0085] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Soak for 300 hours Unshrink Unshrink Unshrink Unshrink Unshrink Soak for 500 hours Unshrink Unshrink Unshrink Unshrink Unshrink Soaking for 1000 hours Unshrink Unshrink Unshrink Unshrink Shrinkage Soak for 2000 hours Unshrink Unshrink Unshrink Shrinkage Shrinkage

[0086] It can be seen from the above table that the present application has a good water resistance effect, and the material will not shrink during long-term immersion, thereby ensuring that the ionized water will not leak out.

[0087] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A hot melt adhesive film for sealing a hydrogen fuel cell catalyst layer, characterized in that: Made by the following steps: The modified resin is dissolved in N-methylpyrrolidone, styrene, ammonium persulfate and sodium bisulfite are added to react, and then reinforcing fillers are added and mixed evenly, and N-methylpyrrolidone is removed by distillation, and the mixture is mixed and pressed into a film; The modified resin is prepared by the following steps: Step A1: 4,4'-dimethylbiphenyl and concentrated sulfur solution are stirred and nitric acid solution is added dropwise to react, then cooled in an ice water bath, and the filtrate is filtered to remove the filtrate to obtain intermediate 1, and intermediate 1, sodium dichromate and deionized water are mixed, stirred, refluxed and concentrated sulfuric acid is added dropwise to react to obtain intermediate 2; Step A2: Mixing intermediate 2, sodium sulfide nonahydrate, sodium bicarbonate and deionized water to obtain intermediate 3, mixing intermediate 3, isophthalic acid, ethylene glycol, diethylene glycol and tetrabutyl titanate to react, and heating to continue the reaction to obtain alcohol ester; Step A3: mixing alcohol ester, acetone, acrylic acid and 1-hydroxybenzotriazole for reaction, removing acetone by distillation, and heating to continue the reaction to obtain a modified resin; The reinforcing filler is prepared by the following steps: Step B1: disperse the porous ceramic powder in deionized water, stir and add KH560, after stirring, filter and remove the filtrate, disperse the substrate in xylene, add KH550, react, and prepare a pretreated filler; Step B2: Disperse the pretreated filler in dimethyl sulfoxide, add KH550, stir, cool and add ammonium fluoride, continue the reaction, and obtain a modified filler; Step B3: Add tetramethylxylene diisocyanate into a reaction kettle, stir and add 3-methyl-1-phenyl-2-phosphole-1-oxide to react to obtain intermediate 4, dissolve intermediate 1 in acetone, add modified filler, and after ultrasonic treatment, filter and remove the filtrate to obtain a reinforced filler.

2. A hydrogen fuel cell catalyst layer sealing hot melt adhesive film according to claim 1, characterized in that: The mass ratio of the modified resin, styrene, ammonium persulfate and sodium bisulfite is 5:20:0.52:0.43, and the amount of the reinforcing filler is 5-8% of the mass of the modified resin.

3. A hydrogen fuel cell catalyst layer sealing hot melt adhesive film according to claim 1, characterized in that: The usage ratio of 4,4'-dimethylbiphenyl, concentrated sulfur solution and nitric acid solution in step A1 is 0.02 mol:50 mL:20 mL, and the usage ratio of intermediate 1, sodium dichromate, deionized water and concentrated sulfuric acid 21 g:98 g:100 mL:200 mL.

4. A hydrogen fuel cell catalyst layer sealing hot melt adhesive film according to claim 1, characterized in that: The molar ratio of intermediate 2, sodium sulfide nonahydrate and sodium bicarbonate described in step A2 is 1:2:1.3, the molar ratio of intermediate 3, isophthalic acid, ethylene glycol and diethylene glycol is 1:1:1.6:2, and the amount of tetrabutyl titanate used is 0.055-0.075% of the sum of the mass of intermediate 3, isophthalic acid, ethylene glycol and diethylene glycol.

5. A hydrogen fuel cell catalyst layer sealing hot melt adhesive film according to claim 1, characterized in that: The molar ratio of the amino group on the alcohol ester, acrylic acid and 1-hydroxybenzotriazole in step A3 is 1:1:1.

1.

6. A hydrogen fuel cell catalyst layer sealing hot melt adhesive film according to claim 1, characterized in that: The amount of KH560 used in step B1 is 5-8% of the porous ceramic powder, and the molar ratio of KH560 to KH550 is 1:

1.

7. A hydrogen fuel cell catalyst layer sealing hot melt adhesive film according to claim 1, characterized in that: The usage ratio of the pretreated filler, KH550 and ammonium fluoride in step B2 is 1 g:5 mL:0.15 g.

8. The hot melt adhesive film for sealing the catalyst layer of a hydrogen fuel cell according to claim 1, characterized in that: The amount of 3-methyl-1-phenyl-2-phospholene-1-oxide used in step B3 is 1-3% of the mass of tetramethylxylylene diisocyanate, and the mass ratio of intermediate 4 to modified filler is 5:1.

Citation Information

Patent Citations

  • Cold-resistant pre-coating agent, hot melt adhesive film and flexible flat cable

    CN109535944A

  • Recovery of 4,4'-biphenyldicarbonacid-dimethylester

    CN1104204A